Retrieval practice benefits memory precision. Issue 8 (14th September 2019) - Schuetze, Brendan A.; Eglington, Luke G.; Kang, Sean H.K.
ABSTRACT: Although previous research on retrieval practice (RP) has predominantly featured stimuli with discrete right-or-wrong answers, continuous measures offer potentially greater sensitivity in assessing the effects of RP on memory precision. The present study used a colour gradient (125 points ranging from magenta to yellow) as a continuous response variable. The colours of different images were learned through either RP or restudy and either one or three cycles of practice after initial study. On a delayed final test, participants' memory was assessed for each item's colour. Participants also created per-item intervals representing the region where they believed the correct colour most likely to have been. We found that repeated rounds of RP enhanced the correspondence between responses and the correct colour. In addition, RP led to participants creating more accurate (correct answers were more likely to be within the participant-specified intervals) and more precise (narrower) intervals relative to restudy, suggesting that RP enhances the precision of memories.